Modeling and Analysis of a Cascaded Battery-Boost Multilevel Inverter Using Different Switching Angle Arrangement Techniques - Tayab, U. B.; Al Humayun, M. A. (Engineering, Technology & Applied Science Research, 2017)
Multilevel inverters have the capability to produce an AC staircase output waveform without using a bulky passive filter. Therefore, the multilevel inverters are gaining more and more popularity, among the different types of inverters, for photovoltaic applications in the modern era of technology. However, if the switching angle arrangement technique is not selected appropriately then the total harmonic distortion of the voltage output waveform may become undesirable. In this paper, Half-Equal-Phase, Feed-Forward and Selective Harmonics Elimination Pulse Width Modulation switching angle arrangement techniques at different power factors (i.e., 1.0, 0.75 and 0.50) are applied to a cascaded battery-boost inverter. PSIM software is used to evaluate and compare the performance of a 9-level cascaded battery-boost inverter with three switching angle arrangement techniques at power factors of 1.0, 0.75, and 0.50, respectively. Simulation results show that the Selective Harmonics Elimination Pulse Width Modulation technique can produce an output voltage and current waveform with the lowest total harmonic distortion. On the other hand, the output current waveform produced by power factor 0.50 had the lowest total harmonic distortion.